La Interculturalidad en el desarrollo social de los niños de 5 años de la Escuela de Educación Básica Chacabamba, parroquia Santiago de Quito, cantón Colta, provincia de Chimborazo octubre 2020- marzo 2021 - Sango Sango, Bethy Amelia (2021)
The present research work understands the importance of interculturality in the social development at 5-year-old children, to analyze interculturality in the social development of children from the Chacabamba Basic Education School. The specific objectives were: To determine the importance, to identify the level and to establish the relationship between interculturality and social development, The theoretical framework contains the authors' criteria with the study object. The field type was the research methodology because it worked with 15 children 5 years, this research work was bibliographic because the information was obtained from special electronic sources. The results made it possible to establish a direct relationship between interculturality and the social development of children. To conclude, interculturality is important in the education of children because of children are different, they come from different cultures, they have attitudes and beliefs and socialization problems, they are different in each one, they presented hostile attitudes towards other children because of product of their cultural heritage and finally Bilingualism is important in the classroom.